Sonoprocessing of LiFePO4 nanoparticles and nanocomposites for cathode material in lithium ion batteries. Issue 6 (30th January 2015) - Bhagawat, L.I.; Patil, V.S.; Kale, B.B.; Sonawane, S.H.; Bhanvase, B.A.; Pinjari, D.V.; Ashokkumar, M.
Abstract : Lithium iron phosphate (LiFePO4 ) nanoparticles and lithium iron phosphate/halloysite (inorganic nanotubes) (LiFePO4 /INT) nanocomposites were prepared by ultrasound‐assisted synthesis in an aqueous solution of lithium hydroxide containing ammonium dihydrogen phosphate and ferrous chloride and used as cathode materials in lithium ion batteries. The performance of the cathode material was measured using cyclic voltammetry. The oxidation potential for LiFePO4 polyaniline/nanotubes/anode cell was found to be in the range of −1.12 to 1.063 V while the reduction potential for lithium iron phosphate cell was in the range of −1.03 to 1.15 V. POLYM. COMPOS., 37:1874–1880, 2016. © 2015 Society of Plastics Engineers